SDGs in Indonesian Biology Teacher Education: A PLO-Based Curriculum Analysis - Aprilisa, Ema; Limiansi, Kintan; Febriyantiningrum, Kuntum (Mahesa Research Center, 2026)
Teacher education plays a strategic role in preparing future educators to address global sustainability challenges articulated in the Sustainable Development Goals (SDGs). This study aims to examine how Biology Teacher Education curricula in Indonesia align with the SDGs through an analysis of Program Learning Outcomes (PLOs). A qualitative case study design was employed using document analysis of PLOs from Biology Education programs at three public universities ranked among the top 20 institutions in Indonesia according to the Scimago Institutions Rankings (SIR) 2025. A benchmarking framework was applied to assess the extent to which PLO indicators support the achievement of the 17 SDGs. The findings reveal varying degrees of alignment across institutions. Research competencies, scientific problem-solving skills, and technology integration demonstrate the strongest alignment with SDG targets, while environmental knowledge and laboratory skills particularly support goals related to quality education, innovation, and environmental sustainability. However, character- and religiosity-oriented outcomes do not explicitly correspond to specific SDG targets, and overall integration remains implicit rather than systematically embedded within the curriculum. These results indicate the need for more explicit curriculum mapping to ensure coherent and comprehensive integration of SDG dimensions in Biology Teacher Education programs.